Programmatic microcosms: modern referential buildings from the urban landscapes of Mozambican colonial cities - Miranda, Elisiário José Vital (2015)
The investment of the Portuguese central government in the infrastructural development of its former African colonies took a wider dimension during the period raging from the end of the II World War and the start of the colonial or liberation war. This process lead to a growth on the programming and construction of infrastructural buildings meant for solving the continuous increase of the local population. What brings unity to this big-scale architecture relies on the training and practice of its authors on the Modern Movement principles, methods and architectonic syntax. The wide diffusion of the modern architecture in the African territories results, on one hand, from the freedom allowed by the official authorities and by the private entrepreneurs on the use of this new syntax and, on the other hand, on its capacity to serve the programmatic, economical, climatic, technological and productive demands of territories going through accelerated growth. Along this paper, two case studies of Mozambican buildings of large scale, great complexity and representativeness will be analyzed: the branch office of BNU, Banco Nacional Ultramarino (Overseas National Bank), in former Lourenço Marques, nowadays the city of Maputo, and the Montegiro Commercial, Touristic and Housing Complex, in Quelimane. Both constituted programmatic microcosms, comprehending spaces of collective use and of private housing; both acted as reference elements in the continuous urban landscapes, symbolizing the modernity, progress and permanence values proclaimed by the Estado Novo fascist regime and expressed by the local colonial societies.